Syntactic analysis in Filipino AFAM hunters facebook group posts - Jily C. Balilo; Kenneth Cole S. Lacsina; Rodolfo P. Dizon Jr (Yayasan Mitra Persada Nusantara, 2026)
Nowadays, by the use of English language on Facebook, Filipinos—especially Filipino AFAM Hunters—are easily able to communicate with foreigners, forging connections through online dating and social interaction. Highlighting global trends, Filipinos more likely to use Facebook, the nation’s most popular social media platform, to interact with various nationalities and express their intentions and emotions. This connects with what Abrazaldo (2023) says about how colonial mentality affects Filipinos' online dating choices, which often leads to relationships with foreigners who are thought to be financially stable and socially mobile. Banuag (2024) and Estremera (2021) both point out that informal language, creative sentence structures, and code-switching are common in these online spaces. This shows that clarity and contextual meaning are more important than strict grammatical rules. This study used Morley’s (2006) syntactic framework and Rahmawati and Rachmi’s (2022) analytical steps, where researchers examined 15 Facebook posts from the Filipino AFAM Hunters group to identify the most common syntactic deviations and patterns from Standard American English. Results from data analysis have revealed that frequent deviations involve punctuation and capitalization errors, run-on sentences, missing articles, and subject–verb disagreement. These data emphasize how users prioritize message clarity over grammatical accuracy, which is normal in informal online communication. The results also indicate that the socio-economic background and age of these users may affect their English proficiency. Finally, the study emphasizes the need for more extensive research in the future to examine more posts across additional social media platforms to have a better understanding of how people linguistically behave in the online landscape.